Penerapan Model Pembelajaran Problem Based Learning Plus Lembar Mudzakarah Dalam Meningkatkan Hasil Belajar Siswa di MAN Kota Cimahi - Iman Zaelani (Community Empowerment)
The learning conditions in the mawaris material, especially in the internal heirs and their sections, previously used a one-way learning style with a very high percentage of the lecture method, this made the learning situation not show high enthusiasm in class XI MIPA 3 MAN Cimahi City, resulting in children's learning outcomes are unsatisfactory. Based on this, the author will apply the Problem Based Learning Model by strengthening mudzakarah sheets on heirs and their parts in class XI MIPA 3 MAN Cimahi City. The aim is to improve the condition of students' low learning outcomes with 39% completeness with a target of 80% completeness. This activity applies classroom action research on fiqh subjects regarding internal heirs and their parts using the Problem Based Learning model plus Mudzakarah Sheet (LM) with three cycles. Each cycle uses four stages, namely planning, action, observing and reflecting. This activity produces an overview of student learning outcomes in the 1st cycle with a completeness level of 39%, the 2nd cycle with 61% completeness and the 3rd cycle 81%. With this increased learning outcome, it can be concluded that the application of the Problem Based Learning Model by strengthening the mudzakarah sheet on heir material and its parts in class XI MIPA 3 MAN Cimahi City can be concluded to improve student learning outcomes.